Existence and Boundedness of Solutions for Nonlinear Volterra Difference Equations in Banach Spaces - Rigoberto Medina (Abstract and Applied Analysis)
We consider a class of nonlinear discrete-time Volterra equations in Banach spaces. Estimates for the norm of operator-valued functions and the resolvents of quasi-nilpotent operators are used to find sufficient conditions that all solutions of such equations are elements of an appropriate Banach space. These estimates give us explicit boundedness conditions. The boundedness of solutions to Volterra equations with infinite delay is also investigated.